Instruments for assessing social health in the context of cognitive decline and dementia: a systematic review - Altona, Janissa; Wiegelmann, Henrik; Lenart-Bulga, Marta; Vernooij-Dassen, Myrra; Verspoor, Eline; Seifert, Imke; Misonow, Julia; Szcześniak, Dorota; Rymaszewska, Joanna; Chattat, Rabih; Jeon, Yun-Hee; Moniz-Cook, Esme; et al. (Frontiers in Psychiatry, 2024)
The concept of social health has recently received increasing attention in dementia research. Various notions of what social health is and how it can be measured are circulating. They may pose challenges for comparing results and interpreting them for the development of interventions. This systematic review aims to classify existing instruments that measure various domains of social health. To achieve this, we applied a new multidimensional framework consisting of six key domains of social health. A systematic review was conducted following the PRISMA 2020 guidelines. PubMed/MEDLINE, PsychINFO, and CINAHL were searched for studies published between January 2000 and July 2023. A total of 227 studies (longitudinal, case–control, and cross-sectional cohort studies) with 102 single instruments were included. The search terms were as follows: (1) dementia (i.e., Alzheimer’s, cognitive impairment); (2) social health markers (i.e., decision-making, social participation, loneliness); and (3) instruments (i.e., tools, measures). The instruments are mainly self-reported, and the number of items ranges from 3 to 126. Despite the wide array of instruments available, most focus on individual domains of social health. We recommend the development of more conceptually robust instruments that can comprehensively evaluate psychosocial interventions and adequately capture all domains of social health.